Odpowiedzialny lobbing jako instrument CSR - Lewicka-Strzałecka, Anna (Annales. Etyka w Życiu Gospodarczym, 2011)
Lobbying in the contemporary world is a recognized instrument for implementing citizen’s right to be represented and to be heard bythe authorities. The goal of lobbying is to pay authorities’ attention to important problems of citizens and organizations, to present variouspoints of view, to provide adequate information and consequently to contribute to the public good. Nevertheless the social image of lobbyistsand lobbying has never been positive and an extreme opinion says that muddy and immoral lobbying is threatening for democracy.This opinion is specially significant in the context of corporate lobbying and because of this various initiatives aimed at restoring a properplace of lobbying in the democratic system are undertaken. The paper presents such initiative, namely an attempt to treat responsiblelobbying as one of the CSR instrument. The author shows both opportunities and limitations of this approach.